Use of Video-Based Instruction With Code-Switching To Improve Students' Attitudes And Performance - Rose Ann Deparon (Philippine Association of Institutions for Research, Inc., 2023)
In a world of extraordinary technological progress, teachers use a variety of ways to provide effective physical education classes. It demanded a transition from traditional to advanced digital learning. This study examined the effect of video-based instruction with code-switching on students' performance and attitudes in Physical Education. The research utilized a quasi-experimental pretest-posttest design with two groups of 78 senior high school students in Bukidnon, Philippines. The data were analyzed using the mean, standard deviation, and analysis of covariance (ANCOVA). The data showed that the performance of the experimental group, who received video-based instruction with code-switching, improved significantly more than the control group from the pre-test to the post-test. However, there was no significant difference in post-test scores in students' attitudes towards the subject between those who received Video-Based Instruction with Code-Switching and those who did not. Consequently, the language used (code-switching) is an effective tool for instruction for improving student performance and attitudes. This paper may serve as a wake-up call for the Department of Education to advocate using local language in all K--12 programs, not just at the primary levels, given that education is essential for building a better nation. PE teachers should take note of these consequences while creating lessons that support learning and cater to the requirements and interests of diverse students.